Atividades experimentais em ciências naturais: uma abordagem da aprendizagem significativa - BELO, Lucidéia Cordeiro (2024)
In order to study experimentation in science teaching, from the perspective of meaningful learning, theory developed by David Ausubel, the present This work highlights that the student, being selective, is not interested in activities that are not attention, which negatively influences the teaching process and learning. Therefore, the relevance of the work consists in considering that through of experimentation in science classes, the student starts to consider this discipline from another perspective, which provides a meaning in its study. To achieve this proposal, the methodology of qualitative characteristic was adopted, which, through bibliographic research, consultations to academic works related to the topic and application of questionnaires aimed at teachers of natural sciences served as a reference for the development of the study. In this way, it was possible contact that experimentation must contain, in its practice, a meaning for the students, that is, going through the knowledge that the student already presents in order to obtain success in the teaching and learning process.